Altered Pulmonary Venous Flow Pattern in Young Adults with Atrial Septal Defect - Parsaee, Mozhgan; Saedi, Sedigheh; Salehi, Nahid; Saedi, Tahereh (International Journal of Cardiovascular Practice, 2016)
Introduction: Atrial septal defect (ASD) is a common congenital heart disease and causes left-to-right shunting and significant right ventricular (RV) volume overload. The goal of this study was to evaluate the influence of these hemodynamic changes on pulmonary venous flow pattern in young adults.Methods: Complete echocardiographic examination was performed in a group of 40 young adults (aged < 40 years) who had secundum type ASD and was compared to 40 age-matched individuals in control group who had no cardiac abnormality. Systolic and diastolic flow velocities in pulmonary veins (PV), superior vena cava (SVC), inferior vena cava (IVC) and RV functional parameters were recorded and evaluated.Results: As opposed to healthy young individuals who showed distinct S and D waves with diastolic predominance in pulmonary vein Doppler, in patients with ASD a continuous flow with increased systolic peak that began in systole and continued to the late diastole was observed. The RV systolic function increased compared to the control group.Conclusions: In patients with ASD, the pattern of pulmonary veins flow transforms into a single continuous antegrade wave with systolic dominance due to persistent shunting of left atrial blood in to right heart chambers as well as increased RV pump function on pulmonary vein (by means of ASD), SVC and IVC, and could be used as a screening method for the presence of secundum type ASDs in young adults.